Variation in shallow sandy loam porosity under the influence of shallow coal seam mining in north-west China. Issue 5 (September 2020) - Cui, Fan; Du, Yunfei; Chen, Baiping; Zhao, Yuxuan; Zhou, Yingqing
To study the influence of coal mining on the porosity of shallow sandy loam under conditions of shallow seam mining in thick, loose layers in north-west China, a typical surface sandy loam stratum in Shaanxi Province was taken as the study area, and experiments were performed to test the variation of soil porosity at different depths of 0–10 m in strata before, during and after mining therein. The experimental results demonstrate that the overall average porosities in the disc-shaped edge area, the disc-shaped edge area to the disc-shaped basin bottom area and the disc-shaped subsidence centre area of shallow sandy loam in mining increased by (23.51, 18.07 and 22.61%) respectively compared with that before mining. Mining meant that the soil porosity in the period of stable subsidence after mining changed significantly in the disc-shaped edge area and the disc-shaped edge to the disc-shaped basin bottom area. The disc-shaped edge area shows a trend of slowly rising porosity with the increase of depth, and the disc-shaped edge area to the disc-shaped basin bottom area shows a trend of gradually increasing first and then gradually becoming stable. Although the porosity in the central area of disc-shaped subsidence increased before mining, its trend was similar to that before mining. Although the change in soil porosity in the period of post-mining settlement stability is greater than that before mining, it is best fitted by a quintic polynomial. In general, the rate of change of soil porosity in the study area shows similar trends with depth. It showed a U-shaped variation that first decreased, stabilised for a distance and then gradually increased. This study provides theoretical support for surface soil remediation and ecological environment restoration in coal mining areas.